Transformative Beauty : Art Museums in Industrial Britain. - Woodson-Boulton, Amy (Stanford University Press, 2012)
Why did British industrial cities build art museums? By exploring the histories of the municipal art museums in Birmingham, Liverpool, and Manchester, Transformative Beauty examines the underlying logic of the Victorian art museum movement. These museums attempted to create a space free from the moral and physical ugliness of industrial capitalism. Deeply engaged with the social criticism of John Ruskin, reformers created a new, prominent urban institution, a domesticated public space that not only aimed to provide refuge from the corrosive effects of industrial society but also provided a rem.